2007
DOI: 10.1016/j.jalgebra.2006.11.044
|View full text |Cite
|
Sign up to set email alerts
|

A geometric construction of finite semifields

Abstract: A finite semifield is shown to be equivalent to the existence of a particular geometric configuration of subspaces with respect to a Desarguesian spread in a finite dimensional vector space over a finite field. In 1965 Knuth \cite{Knuth1965} showed that each finite semifield generates in total six (not necessarily isotopic) semifields. In certain cases, the geometric interpretation obtained here allows us to construct another six semifields, providing a link between some known examples which are not related by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 13 publications
(9 reference statements)
0
59
0
Order By: Relevance
“…So for r = n, the approach using the representation of the subspaces as U f and W g , is the same as in the proof of [3,Theorem 4.1]. But the advantage of the viewpoint taken here is that this explicit multiplication can not only be obtained for r = n, but for any r ≥ 2.…”
Section: Bel-constructionmentioning
confidence: 99%
See 3 more Smart Citations
“…So for r = n, the approach using the representation of the subspaces as U f and W g , is the same as in the proof of [3,Theorem 4.1]. But the advantage of the viewpoint taken here is that this explicit multiplication can not only be obtained for r = n, but for any r ≥ 2.…”
Section: Bel-constructionmentioning
confidence: 99%
“…So, as was shown in [3], the switching operation can be applied to rank two semifields. In [11], it was shown that in this special case, switching has a geometric interpretation ("dualising an ovoid").…”
Section: Rank Two Semifieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section we concentrate on a geometric construction of finite semifield spreads. The construction we give here is taken from [47], but the main idea is the slightly less general construction given in [9] (where L is a subspace, i.e. t = 1).…”
Section: Rank Two Commutative Semifields (Rtcs)mentioning
confidence: 99%